Mobility in vehicular networks with dynamic connectivity and load balancing - Oliveira, Marco Rafael Tenrinho (2018)
With the evolution of technology and the demands of population, the technological advances are leading to the so called internet of things and, in its turn, the development of the internet of things leads to the creation of new objectives and to the utilization of new approaches regarding access networks. Besides, the stable communication is also desired independently of the access technology in use. Nowadays the importance of being connected always and everywhere is increasing, independently of the access conditions. The usage of vehicular networks is getting to a reality, and they are used with several objectives and providing several services. In this way, this kind of networks can already provide services to the community like internet connection inside the vehicle, gather data from the city and, when the deployment extends to common users, some features like road safety and autonomous driving will be possible. With the dynamicity of these networks it is usual that one node is in reach of more than one access point, but when this happens, that node will just connect to one of them independently of the good quality of those access points. Besides, with the high mobility of the nodes in the network, the amount of changes in the way the network is connected is high, which leads to the importance of having always a good connection and a fast change between networks when needed. This dissertation focuses on the need to guarantee that one node connects simultaneously to several access points to the network and providing fast mobility of the nodes in a transparent manner to the users. Therefore, the integration between the N-PMIPv6 mobility protocol and a PMIPv6 multihoming support extension is performed. Several entities that support multihoming are integrated and adapted to the characteristics/operation of N-PMIPv6 in the way that they are as adapted as possible to the vehicular conditions. Also, a particularity of the WAVE vehicular technology is used so that one interface can connect to more than one access point at the same time. Besides, the traﬃc to the users is distributed in such a way that it accounts for the characteristics of the networks and of that same traﬃc. Regarding the connections performed, the entity that manages them is improved so that it can support more than one at the same time. Finally, a mobility protocol for vehicular networks is obtained that supports simultaneous connections to the network, in which those connections can be seen and treated as belonging to the same user. Besides, the laboratory and road tests show that a division of the traﬃc through the several paths is performed in a way that it minimizes delay, maximizes the utilization of WAVE and minimizes the possible out-of-order packets.